Pemberdayaan Remaja Masjid Berbasis Wirausaha untuk Meningkatkan Perekonomian Masjid - Zaharuddin, Zaharuddin; harahap, Uun Novalia; Utama, Denny Walady; Hasibuan, Yetti Meuthia; Syarif, Abdul Azis (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
Community service is an integral part of the Tri Dharma of higher education, aiming to contribute positively to society. Masjid Silaturahim has faced challenges in achieving financial independence, limiting its ability to provide comfortable facilities for congregants. Additionally, mosque youth lack entrepreneurial spirit and opportunities to develop their potential. The objectives of empowering mosque youth is to enhance mosque financial independence through entrepreneurship managed by mosque youth and developing creativity and innovation in entrepreneurship among mosque youth. Therefore, empowering mosque youth employed a community-based research approach providing education and information on designing and constructing a soap mixer machine.producing liquid dishwashing soap and calculating production costs. The outcomes from this activity are mosque youth can manage a mosque-based entrepreneurship venture by producing and marketing liquid dishwashing soap to be marketed in the community around the Silaturahim Mosque (Jalan Tangguk Bongkar) and traditional markets as well as increased mosque revenue through product sales